The analysis of medical prescriptions for patients with duodenal ulcer in hospital setting - Balitska, O. P.; Balynska, M. V.; Zlahoda, V. S.; Haiday, O. D.; Blahun, O. D.; Ischenko, V. O. (Social Pharmacy in Health Care, 2024)
Aim. To analyze medical prescriptions for patients with duodenal ulcer disease in hospital setting, to determine the compliance of the treatment with the current treatment protocols. Materials and methods. We used 102 case histories, medical prescriptions of the Gastroenterology Department of the Clinical Regional Hospital named after M.I. Pirogov, Unified Clinical Protocol of the primary and specialized medical care “Peptic ulcer of the stomach and duodenum in adults and children”, the State Formulary of Medicines of Ukraine, the nomenclature of drugs for the treatment of duodenal ulcer, the official online resource tabletki.ua. Statistical, analytical and comparative, systematic, logical, graphic and mathematical-statistical methods were applied. Results and discussion. As a result of the study conducted, an analysis of drug prescriptions for patients with duodenal ulcer was carried out at the premises of the Gastroenterology Department of the Clinical Regional Hospital named after M. I. Pirogov. Over a period of 1 year and 3 months, 102 patients with the main diagnosis of duodenal ulcer were treated. According to the data obtained from the histories of diseases, men (94 %) aged 30-40 years were most often ill. The average duration of bed days was 5 days. The most common concomitant diseases were pancreatitis, GERD (non-erosive, endoscopically positive), hepatitis, duodenal bile reflux, Oddi sphincter dysfunction (pancreatic type). Two groups of drugs were prescribed according to the ATC classification for pathogenetic and symptomatic treatment: group A – drugs affecting the digestive system and metabolism (71.43 %) and group J – antimicrobial drugs for systemic use (28.57 %). Among the producing countries, foreign-made drugs prevailed – 62.4 %. During the study period, doctors prescribed 63 active substances by INN and 109 drugs by TN. In accordance with the Unified Clinical Protocol, the number of INN drugs was 18, 39 drugs by TN, and the State Formulary included drugs of 48 INN and 80 TN. During the study period, 24 drugs by TN for the pathogenetic treatment (eradication therapy) and 18 drugs by TN for the symptomatic treatment were prescribed. The prescription of drugs for the pathogenetic and symptomatic treatment was scientifically substantiated and included in the current normative documentation for the provision of patients with duodenal ulcer. When conducting the eradication therapy the leading drugs were Omeprazole (66 prescriptions), De-nol (55 prescriptions), Ezonexa (29 prescriptions), Controlok (26 prescriptions), Pilobact Neo (24 prescriptions). To prevent dysbiosis, such drugs as Enterol (8 prescriptions), Enterogermina forte (7 prescriptions) were most often prescribed. To relieve the symptoms of duodenal ulcer, Mebsyn Retard (24 prescriptions), Trimspa (19 prescriptions), Neospastil (17 prescriptions) were applied. Conclusions. Therefore, the medical care of patients in hospital setting is expedient and corresponds to the current Treatment Protocols.